Quorum Sensing Signaling Alters Virulence Potential and Population Dynamics in Complex Microbiome-Host Interactomes - Reen, F. Jerry; Gutiérrez-Barranquero, José A.; McCarthy, Ronan R.; Woods, David F.; Scarciglia, Sara; Adams, Claire; Fog Nielsen, Kristian; Gram, Lone; O’Gara, Fergal (Frontiers in Microbiology, 2019)
Despite the discovery of the first N-acyl homoserine lactone (AHL) based quorum sensing in the marine environment, relatively little is known about the abundance, nature and diversity of AHL quorum sensing systems in this diverse ecosystem. Establishing the prevalence and diversity of AHL QS systems and how they may influence population dynamics within the marine ecosystem, may give a greater insight into the evolution of AHLs as signalling molecules in this important and largely unexplored niche. Microbiome profiling of sponge samples identified several potential QS active genera. Subsequent biosensor-based screening of a library of 650 marine sponge bacterial isolates identified 10 isolates that could activate at least one of the three biosensor strains. Each was further validated and profiled by Ultra-High Performance Liquid Chromatography Mass Spectrometry, with AHLs being detected in 8 out of 10 isolate extracts. Co-culture analysis with QS isolates and marine sponge samples led to the isolation of genera such as Pseudomonas and Paenibacillus from the marine sponge Stelletta normani. Surprisingly however, addition of AHLs to these isolates did not affect either growth or biofilm. Addition of supernatants from QS active strains did however impact significantly on biofilm formation of the marine Bacillus subtilis CH8a biofouling strain suggesting a role for QS systems in moderating the microbe-microbe interaction in marine sponges. Genome sequencing and phylogenetic analysis of a QS positive Psychrobacter isolate identified several QS associated systems, although no classical QS synthase gene was identified. The stark contrast between the biodiverse sponge microbiome and the relatively limited culturable profiles obtained even in the presence of QS active compounds, serves to underscore the extent of diversity that remains to be brought into culture.